Kajian Strategi Manajemen Pemasaran Gula Kelapa Kristal Organik di Koperasi Wanita Srikandi Purworejo, Jawa Tengah dengan Menggunakan SWOT Analisis - Susanto, Hanggoro; Rizqiyani, Septika (Universitas Islam Kadiri, 2025)
Koperasi Wanita Srikandi is an agribusiness cooperative engaged in coconut commodities, particularly coconut crystal sugar, which has strong market potential due to its health benefits. With increasing competition in domestic and international markets, the cooperative must develop effective marketing strategies to secure a profitable position. This study aims to identify internal and external factors affecting the marketing of coconut crystal sugar, formulate alternative strategies, and determine strategic priorities. A descriptive method was used, involving 14 key informants selected through purposive sampling—individuals knowledgeable about the cooperative’s marketing. Data were collected through interviews conducted from March to June 2024 and analyzed using the IFE, EFE, IE, SWOT matrices, and QSPM. The results show that the main strengths are certifications such as Fair For Life (FFL) and Regenerative Organic Certified (ROC), along with strict product quality control. The primary internal weakness is the lack of employment continuity among factory workers. Externally, the abundance of farmers presents an opportunity, while the main threat is the difficulty of regenerating penderes (sap tappers). Based on QSPM analysis, the top-priority strategy is market expansion to strengthen competitiveness and sustainability.